A Genomewide Screen for Suppressors of par-2 Uncovers Potential Regulators of PAR Protein-Dependent Cell Polarity in Caenorhabditis elegans - Labbé, Jean-Claude (Copyright © 2006 by the Genetics Society of America, 2006)
The PAR proteins play an essential role in establishing and maintaining cell polarity. While their function is conserved across species, little is known about their regulators and effectors. Here we report the identification of 13 potential components of the C. elegans PAR polarity pathway, identified in an RNAi-based, systematic screen to find suppressors of par-2(it5ts) lethality. Most of these genes are conserved in other species. Phenotypic analysis of double-mutant animals revealed that some of the suppressors can suppress lethality associated with the strong loss-of-function allele par-2(lw32), indicating that they might impinge on the PAR pathway independently of the PAR-2 protein. One of these is the gene nos-3, which encodes a homolog of Drosophila Nanos. We find that nos-3 suppresses most of the phenotypes associated with loss of par-2 function, including early cell division defects and maternal-effect sterility. Strikingly, while PAR-1 activity was essential in nos-3; par-2 double mutants, its asymmetric localization at the posterior cortex was not restored, suggesting that the function of PAR-1 is independent of its cortical localization. Taken together, our results identify conserved components that regulate PAR protein function and also suggest a role for NOS-3 in PAR protein-dependent cell polarity.